Use the properties of real numbers to simplify the following expressions:
2a(a – 5) + 4(a – 5)

2a(a – 5) + 4(a – 5) =2a^2 - 10a + 4a - 20 =2a^2 - 6a -20

Question

Asked 10/13/2013 9:54:25 PM

Updated 6/10/2014 1:42:29 PM

1 Answer/Comment

Flagged by debnjerry, Edited by andrewpallarca [6/10/2014 1:42:26 PM], Unflagged by andrewpallarca [6/10/2014 1:42:29 PM]

Rating

3

2a(a – 5) + 4(a – 5)

=2a^2 - 10a + 4a - 20

=2a^2 - 6a -20

=2a^2 - 10a + 4a - 20

=2a^2 - 6a -20

Added 10/13/2013 10:31:43 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/10/2014 1:42:17 PM]

27,097,795

questions answered

There are no comments.